Charge storage in KCu7S4 as redox active material for a flexible all-solid-state supercapacitor - Dai, Shuge; Xu, Weina; Xi, Yi; Wang, Mingjun; Gu, Xiao; Guo, Donglin; Hu, Chenguo (Nano energy, 2016)
Supercapacitors are promising devices for highly efficient energy storage and power management. A notable improvement in performance has been achieved through recent advances in understanding charge storage mechanism and the development of advanced nanostructured materials. Here, by combining experimental and theoretical investigations, we have unveiled the detailed charge storage mechanism of KCu7S4 wires based on a flexible all-solid-state supercapacitor. KCu7S4 with a unique double-tunnel structure and excellent conductivity exhibits outstanding properties as an electrode material in supercapacitors. Both electrochemical experiments and DFT calculations show that the stable energy storage process is mainly contributed by potassium ions׳ insertion/extraction, where potassium ions are proved to have been more active than lithium ions in the redox reactions on the KCu7S4 electrodes. The flexible supercapacitor based on the KCu7S4/Graphene paper is low-cost, easy to fabricate and environmentally friendly. The understanding for the charge storage presented in this work would guide the improvement on supercapacitor and exploration of new electrode materials. KCu7S4 with unique double-tunnel structure and excellent conductivity exhibits outstanding properties as a redox active material in supercapacitors. The diffusion paths of K+, Li+ and H+ in the KCu7S4 tunnels are reported based on the density functional theory, thermodynamic analysis and nudged elastic band method. [Display omitted] •KCu7S4 with unique double-tunnel structure and excellent conductivity exhibits outstanding electrochemical properties.•The diffusion paths of K+, Li+ and H+ in the KCu7S4 tunnels are reported based on the theoretical analysis.•A highly flexible all-solid-state supercapacitor is fabricated based on the KCu7S4/Graphene paper electrodes.